Fast prototyping of microtubes with embedded sensing elements made possible with an inkjet printing and rolling process. (29th December 2017) - Wang, N; Meissner, M V; MacKinnon, N; Luchnikov, V; Mager, D; Korvink, J G
Abstract: We present a new fabrication process to create sub-mm micro tubes with embedded conductive patterns. Based on common 2D patterning techniques and a specially designed rolling process, it achieves 3D structures featuring potentially complex, embedded electrical, mechanical and micro-fluidic functions. We demonstrate the advantage in creating freeform electrical conductors around sub-mm tubes, such as needed for a tube-integrated micro heater. The production of the 2D patterns is flexible, and we demonstrate that both additive manufacturing (fast, accessible) and conventional micro-fabrication processes (cleanroom, wafer-scale) are compatible with the rolling process. To adapt the rolling process for high frequency applications, the patterned tracks can be directly electroplated, with good adhesion, to reduce electrical resistance. For the first time, we achieve saddle-geometry NMR micro detectors. They feature 100 μ m wide, 10 μ m thick conductive tracks on 25 μ m thick polyimide film, and were successfully tested in a 500 MHz (11.7 T) NMR spectrometer. Using a 620 μ m diameter coil, we measured the single-shot SNR of deionized water sample, which corresponded to a mole sensitivity of 18.78 n m o l H z − 1 / 2, and a water line shape of 1.52/26.8/37.3 Hz (50, 0.55, 0.11% of the maximum height) from a sample volume of only 82 nl.